2015
DOI: 10.1039/c4nr07618d
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of the effect of purity on the properties of single wall carbon nanotubes

Abstract: We quantitatively demonstrate the importance of high purity for the application of single wall carbon nanotubes (SWCNTs), materials solely composed of one surface, by examining the effects of carbon impurities on the electrical, thermal, and mechanical properties of both as-grown SWCNT forests and processed buckypaper. While decreases in properties were expected, our results showed the extreme sensitivity of SWCNT properties to carbonaceous impurities either through scattering in the individual SWCNTs or an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 49 publications
(105 reference statements)
1
11
0
Order By: Relevance
“…The increase in the D peak intensity observed in case of evaporated carbon coated samples could be attributed to the presence of amorphous carbon layer which has a behaviour similar to the carbonaceous impurities as shown in the literature. 23 The intensity of RBM and G peak also reduces in comparison to the pristine sample due to the evaporated carbon film as shown in the literature. 23 From the SEM images and TEM micrographs (see supplementary Fig.…”
Section: B Evaporated Carbon Coated Samplesmentioning
confidence: 71%
See 1 more Smart Citation
“…The increase in the D peak intensity observed in case of evaporated carbon coated samples could be attributed to the presence of amorphous carbon layer which has a behaviour similar to the carbonaceous impurities as shown in the literature. 23 The intensity of RBM and G peak also reduces in comparison to the pristine sample due to the evaporated carbon film as shown in the literature. 23 From the SEM images and TEM micrographs (see supplementary Fig.…”
Section: B Evaporated Carbon Coated Samplesmentioning
confidence: 71%
“…23 The intensity of RBM and G peak also reduces in comparison to the pristine sample due to the evaporated carbon film as shown in the literature. 23 From the SEM images and TEM micrographs (see supplementary Fig. S1 24 ), it was observed that the evaporated carbon film forms a coating on the SWCNTN.…”
Section: B Evaporated Carbon Coated Samplesmentioning
confidence: 71%
“…Using both TGA and nitrogen adsorption purity analysis techniques, the highest reported purity for SWCNTs was 99.98% carbon purity and a specic surface area $1250 m 2 g À1 . 6,32,33 Therefore, the reported carbon purity of 99.3% and specic surface area 1180 m 2 g À1 stands among the highest reported.…”
Section: Puritymentioning
confidence: 94%
“…17 Carbonaceous impurities also deteriorate the electrical, thermal, and mechanical properties of CNTs. 18 Moreover, research has come to light that the initial claims regarding the outstanding electrochemical performance of CNTs with applications in sensors and energy storage, are influenced by the CNT impurities. [19][20][21] Therefore, various processes are developed and implemented to remove the impurities.…”
Section: Impuritiesmentioning
confidence: 99%